Monitoring of air quality with satellite-based sensor: The case of four towns in Southeast, Nigeria - Francis Olawale Abulude; Sunday Acha; Kikelomo Mabinuola Arifalo; Akinyinka Akinnusotu; Samuel Dare Oluwagbayide; Baig Abdullah Al Shoumik; Arinola Oluwatoyin Gbotoso (ASEAN Journal of Science and Engineering, 2023)
Air pollution is an important issue globally because it is linked to health risks or death as the case may be. No nation has placed a carefree attitude on the menace. Constant monitoring to reduce or bring it to an end is on the increase. Internet of Things (IoT) is one of the tools used in monitoring air quality. The main functionality of IoT includes sensing out the surrounding environment collecting the data from the surrounding and transmitting those data to the remote data centers or the cloud. In this study, Satellite model information provided by Plume Labs, Paris, France was used for the determination of the air quality in four towns (Owerri, Awka, Aba, and Nsukka) in the Southeastern part of Nigeria. The data were obtained from the Plume Labs website between the hours of 6-9 am and 7-9 pm every day for a period of sixty (60 days). The air qualities of the towns were obtained by comparing the satellite results with Plume Air Quality Index Indicator (PAQI). PAQI has seven levels (Low, Moderate, High, Very High, Excessive, Extreme, and Airpocalypse) of pollution which are linked to the World Health Organization (WHO) limits. The results depicted that the air quality of the cities has reached elevated levels of pollution above the 24-hour daily limit set by the WHO, which is an indication that everyone may start to experience serious health effects. A long-term exposure constitutes a real health risk.